The Differences Between Preterm and Term Birth Affecting Initiation and Completion of Toilet Training Among Children: A Retrospective Case-Control Study - Yildiz, Dilek; Suluhan, Derya; Eren Fidanci, Berna; Mert, Merve; Tunc, Turan; Altunkaynak, Bulent (Urology Journal, 2019)
Purpose: This study seeks to investigate the possibility the existence of a difference in terms of start and end dates of toilet training between term and preterm children as well as the possible determining factors. Materials and Methods: This study was conducted as a 5-year retrospective case (children born preterm-(32 to <37 weeks) – and control (children born at term (>37 weeks + 1 day)) study. The data were collected with a form consisted of questions about demographic data (12 questions) and toilet traning features (10 questions) through face-to-face interviews with the mothers. A chi-square test and logistic regression analysis were conducted to examine the data. Odds ratio was used as a measure of the relation between levels of the dependent variable. p< .01 and p< .05 values were assumed to be statistically significant. Results: The study examined a total of 133 children including 59 preterm children and 74 children born at term including 60 (45.1%) boys and 73 (54.9%) girls. The possibility of starting toilet training at or before 24 months was found to be 6.4 times greater in full-term children than preterm children (OR=6.493). The logistic regression analysis, which aimed at identifying any variables that might affect end date of toilet training, found that despite the tendency to consider preterm birth as a factor prolonging the duration of toilet training, the difference was not found to be statistically significant (p= .07). Conclusion: This study compared full-term and preterm children in terms of start and end dates of toilet training and found that preterm children start toilet training later than full-term children. Based on the results of the study, it is possible to say that preterm birth, gender and birth order affect start date of toilet training. However there is no difference between term and preterm babies on the end date of toilet training.